CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, NET INTEREST MARGIN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN LOAN TO DEPOSIT RATIO TERHADAP FINANCIAL DISTRESS - Baiq Defika Zahronyana; Dewa P.K. Mahardika (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2018)
The purpose of this research is to determine the effect of CAR, NPL, NIM, BOPO, LDR on the fianancial distress of BUMN Commercial Bank either simultaneously or partially. BUMN Commercial Bank in 2012-2016 was selected as a research population. The purposive sampling technique was used for sampling and obtained samples as much of 4 companies with a five-year period every three months, resulting 80 data to be observed. The Model analysis in this research is logistic regression by using software SPSS 20. The results showed that the variables CAR,NPL,NIM,BOPO,LDR simultaneously affect the financial distress. Partially NPL,NIM, and BOPO variables don’t have effect on financial distress, while CAR variable has significant negative has effect to financial distress and LDR variable significant positf has effect on financial distress.